Validation of a green spectrophotometric method for the determination of dropropizine in commercial oral solutions - Millena Almeida Monsores; Mikaelly Pereira Caet; Anna Karolina Mouzer Machado; Marina Cardoso Nemitz; Vítor Todeschini; Maximiliano da Silva Sangoi (Drug Analytical Research, 2020)
The present work describes a first-order derivative spectrophotometric (1D-UV) method for determination of dropropizine in commercial oral solutions. The method was developed using ecologically correct solvents and validated according to International Conference on Harmonization (ICH) recommendations. The response was linear in the concentration range of 6–24 μg/mL (r = 0.9997, n = 7) at wavelength 249 nm, which was the zero crossing point of excipient solutions. The detection and quantitation limits were 0.36 and 1.18 μg/mL, respectively. The method showed adequate precision, with a relative standard deviation values lower than 1.41%. Excellent values of accuracy were obtained, with a mean value of 99.44%. The method proved to be robust by a full factorial design evaluation. It is simple, it has low cost, and it has low use of polluting reagents. Minimum environmental hazards observed and the results obtained attest to the reliability of the proposed green method, showing to be specific, linear, precise, accurate and robust. Thus, the validated 1D-UV spectrophotometric method was successfully applied to the quantitative analysis of dropropizine in oral solutions dosage forms, helping to improve quality control and to assure therapeutic efficacy.